2018
DOI: 10.1038/emm.2017.287
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Na+−K+-ATPase signaling in renal proximal tubule contributes to hyperuricemia-induced renal tubular injury

Abstract: Hyperuricemia contributes to renal inflammation. We aimed to investigate the role of Na+–K+–ATPase (NKA) in hyperuricemia-induced renal tubular injury. Human primary proximal tubular epithelial cells (PTECs) were incubated with uric acid (UA) at increasing doses or for increasing lengths of time. PTECs were then stimulated by pre-incubation with an NKA α1 expression vector or small interfering RNA before UA (100 μg ml−1, 48 h) stimulation. Hyperuricemic rats were induced by gastric oxonic acid and treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…However, it is possible that the H + , K + -ATPase α subunit is essential in other organs under more strenuous physiological conditions. For example, impairment of this protein in the renal proximal tubule is known to contribute to hyperuricemia-induced renal tubular injury [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that the H + , K + -ATPase α subunit is essential in other organs under more strenuous physiological conditions. For example, impairment of this protein in the renal proximal tubule is known to contribute to hyperuricemia-induced renal tubular injury [22].…”
Section: Discussionmentioning
confidence: 99%
“…So far what we know is that the excretion of urinary sodium and potassium is positively related to hypertension [12,13]. In the previous basic study, we found that uric acid plays a down-regulated function in the NKA activity and its α1 subunit subcellular expression as well as the descending of the intracellular ATP, cell injury and the further activation of Src, NLRP3 and IL-1β [7]. Further, dysfunctional NKA caused by defected membrane of renal tubular cells result in diminished Na + reabsorption and urinary concentration ability [14].…”
Section: Discussionmentioning
confidence: 93%
“…In fact, the driving force of urate transporters in renal tubules comes from its basolateral Na + -K + -ATPase too. Furthermore, the NKA/Src complex has been shown to be activated in the kidney to address excess salt, and the tradeoff could be the development of salt-induced hypertension [7].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that reduction of Na/K-ATPase could significantly attenuate the Na/K-ATPase-related signaling in kidney proximal tubule cells, and potentiate the cell apoptosis [ 25 , 31 ]. A recent publication also demonstrated that impairment of Na/K-ATPase signaling may contribute to hyperuricemia-induced renal tubular injury [ 26 ]. Decrease of Na/K-ATPase is also a common phenomenon in patients with congestive heart failure [ 20 , 32 ], aging [ 33 , 34 , 35 ], diabetes with hypertension [ 36 , 37 , 38 ], and neurological disorders [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from clinical research showed that cardiac contractility is positively correlated with Na/K-ATPase levels in heart failure patients [ 20 , 21 ]. It was also demonstrated that signaling mediated by Na/K-ATPase α1 regulates renal and cardiac cell survival in vitro and associates with renal and cardiac function in vivo [ 22 , 23 , 24 , 25 , 26 , 27 ]. Na/K-ATPase expression can be regulated by multiple transcriptional factors and a variety of chemical compounds [ 28 ].…”
Section: Introductionmentioning
confidence: 99%